Consistency and Variation in Natural Selection on Personality Across 17 Countries - Janko Međedović (Evolutionary Psychology)
The effects of natural selection on personality traits are still understudied, which is in contrast with their importance for analyzing the evolution of personality. In the present research, we analyzed natural selection on the Big Five personality traits by estimating the relations between personality characteristics and evolutionary fitness (reproductive success: i.e., number of children) using the World Values Survey wave 6 data ( N  = 22,636; 17 countries). Using multilevel Poisson regression models with random slopes, we obtained a positive linear association between conscientiousness and reproductive success. We also detected a nonlinear association between openness and the criterion measure: additional graphical and ANOVA analyses showed that nonlinearity emerged from the fact that only individuals with above average openness had lower reproductive success. The effect sizes of the associations between personality traits and reproductive success were low. Finally, we detected variation in selection gradients (i.e., differences in fixed model coefficients) across the countries—coefficients with both positive and negative signs are estimated for extraversion, neuroticism, and openness. This variation is in accordance with the state-dependent models of personality evolution, where environment is viewed as an external state—the environment's moderating effect on the personality-fitness link may preserve inter-individual variation in behavior within and between the populations.